Azobenzene-functionalized graphene nanoribbons: bottom-up synthesis, photoisomerization behaviour and self-assembled structures. Issue 31 (6th May 2020) - Shangguan, Zhichun; Yu, Chunyang; Li, Chen; Huang, Xianhui; Mai, Yiyong; Li, Tao
Abstract : We show the strategy of introducing azobenzene groups into graphene nanoribbons (GNRs), which not only endows GNRs with fast photo-responsiveness but also induces the self-assembly of the GNRs into ultra-long nanowires. Abstract : Azobenzene-functionalized graphene nanoribbons (GNRs) were synthesized through acid promoted alkyne benzannulation. The resulting GNRs showed high dispersibility in common organic solvents (up to 100 mg mL −1 in chlorobenzene) and underwent fast photoisomerization. A photostationary state was established in solution upon 365 nm light irradiation for 20 s and subsequently the initial state could be easily restored upon 500 nm light irradiation for 40 s. Photo-responsive GNR thin films were also prepared by spin coating. Moreover, the azobenzene-functionalized GNRs could self-assemble into nanowires with lengths ranging from several to tens of micrometers. This study opens an avenue for the functionalization of GNRs with stimuli-responsive functional groups, which holds great promise for applications in optoelectronic devices.